(untitled) (Journal of Asian Development Studies, 2023)
This paper attempts to analyze the efforts of the Taliban government for the recognition of its government through diplomatic processes and bilateral and multilateral engagements with other states. The mention of governments under international law has no specific rules and regulations. Still, the states worldwide recognize a government according to their previous policies towards the group, now ruling, and national interests. Furthermore, some principles like legality and affective rule exist, among others, that are often considered preconditions for the recognition of the government. In the case of Afghanistan, countries around the world have put forward some conditions like civil liberties, women’s education, inclusive government, and prevention of the Afghan soil being used for international terrorism. Despite all these factors, the Taliban government is trying to engage foreign states officially and receive formal recognition. They had some engagements even before they were in government and when the Doha peace process was underway with countries like Pakistan, China, and Qatar. After their takeover of Kabul, they initiated a rapid process of foreign engagements and strived hard to establish formal relations with other states. Despite their worries and reservations, countries around the world, even the US-led countries, have informal political and economic engagements with the Taliban but are "waiting" for the right time to recognize their government as legitimate. The paper is primarily qualitative and contributes to the understanding and knowledge regarding Afghanistan and the Taliban government.